Association between serum PLP levels and the natural resolution of nausea and vomiting in pregnancy: a secondary analysis - Gao, Zhuwei; Yu, Hong; Yu, Jiannan; Cong, Jing; Feng, Jiaxing; Yao, Yu; Li, Zihan; Shi, Baichao; Lu, Fengjuan; Wu, Xiaoke; Gao, Jingshu (Frontiers in Nutrition, 2026)
BackgroundNausea and vomiting in pregnancy (NVP) are common clinical symptoms in early gestation. Although vitamin B6 supplementation has been shown to alleviate NVP, the physiological significance of its active form, pyridoxal 5′-phosphate (PLP), and its association with the natural course of symptom resolution remain unclear.ObjectiveTo investigate the association between serum PLP levels in early pregnancy and the natural resolution of NVP, and to elucidate its potential physiological mechanisms to support individualized intervention strategies.Methods352 pregnant women with NVP symptoms were enrolled at ≤12 gestational weeks. The exposure variable was serum PLP concentration, categorized into quartiles (Q1–Q4). The primary outcome was the time to spontaneous NVP resolution, defined by a “7-day confirmation criterion.” Cumulative remission rates were compared across quartiles using Kaplan–Meier analysis. Multivariate Cox proportional hazards models were constructed with stratified control for treatment arms (A–D), and restricted cubic spline (RCS) functions were applied to examine potential dose–response relationships.ResultsKaplan–Meier analysis revealed significant differences in cumulative remission rates among PLP quartiles (log-rank p = 0.00082). Compared with Q1, participants in Q4 showed a 46% lower risk of persistent symptoms (HR = 0.54, 95% CI: 0.38–0.77, p < 0.001). In Model 3, the protective association remained independent and significant (HR = 0.60, 95% CI: 0.42–0.86, p = 0.006). RCS analysis indicated a linear dose–response relationship between PLP and time to remission (Poverall < 0.01, Pnonlinear > 0.4).ConclusionHigher serum PLP levels in early pregnancy were significantly associated with a faster rate of spontaneous remission of NVP. The observed linear association suggests that the active form of vitamin B6 may regulate NVP progression, reflecting the biochemical basis of natural symptom resolution. PLP may be a potential biomarker for evaluating NVP severity and predicting individualized therapeutic response.